Prevalence of High Fat Sugar Salt Products, Labeling Characteristics, and Categories of Foods Sold within In-Store Restricted Areas: A Survey in 3 UK Supermarkets after the 2022 Implementation of the Food (Promotion and Placement) Regulations - Ella Hurst; Sally G Moore; Lewis W Wallis (Current Developments in Nutrition)
Background: Regulations restricting the promotion of some less-healthy products high in fat, sugar, or salt (HFSS) within “restricted areas” (RAs) of supermarkets came into force in October 2022 in England. Objectives: To evaluate the prevalence of HFSS products and front-of-pack nutrition labeling (FOPNL) characteristics of foods sold within RAs in a sample of supermarket stores. Methods: A cross-sectional survey of products in RAs in 3 supermarkets was undertaken from November 2022 to February 2023 using photographs, recording the display of FOPNL. Identified via the online supermarket, product nutrition and ingredient data were collected and used to categorize each as either “in” or out-of-scope of the regulations. The UK Nutrient Profiling Model was used to determine product HFSS status and the FOPNL multiple traffic light criteria used to calculate the number of inherent red traffic lights (iRTLs) possessed. Prevalence of HFSS, FOPNL, and iRTLs were calculated as a proportion (%) of total products. Associations between these characteristics were explored using chi-squared tests. Results: A total of 86 RAs were identified across the 3 stores, of which 32 displayed 679 food products. Most of these products fell into categories considered out-of-scope of the regulations (64%, n = 435) with prevalence of HFSS at 42% (282 of 435 products). For products within in-scope categories, 17% were HFSS (42 of 245). Half of all included products (53%, n = 357) displayed FOPNL, and 16% possessed 1–3 iRTLs, including both HFSS and non-HFSS items. HFSS products in categories in-scope of the regulations were less likely to display FOPNL compared with non-HFSS products (X2 =25, P < 0.001). Conclusions: After the implementation of The Food (Promotion and Placement) Regulations, foods sold in RAs of 3 supermarkets included those in categories in- and out-of-scope, a variable prevalence of less-healthy (HFSS) products, display of FOPNL, and possession of iRTLs. Findings and approach support future impact evaluation.